Too much of a kind - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
While fishing in the Ogooué, Gabon s largest river, you will most likely catch no name (Heterotis niloticus). The fish, which can reach a length of up to 1 meter, is a filter feeder, eating plankton and algae. The no name was released in the early...